FORMING STUDENTS' MOTIVATION TO STUDY FOREIGN LANGUAGES - Жукова, Тетяна Василівна; Zhukova, Tetiana (Vancouver, Canada, 2023)
The work is devoted to the problem of developing students’ motivation to study foreign languages. Importance of organizing the educational process in increasing learners’ motivation is considered in the article. Some motivational strategies are substantiated.
Формування мотивації учнів вивчати іноземні мови.
Keywords: motivation; innovative technologies; encouragement; academic goals; professional development; assessment